Integrated medical and nursing ward rounds for an elderly patient with chronic renal failure guided by Traditional Chinese Medicine theory (1例以中医理论为指导的老年慢性肾衰竭患者医护一体化查房体会) - LI Xiuli (李秀丽); LI Yuanyuan (李媛媛); XIE Xuan (谢璇); DENG Jianhua (邓建华) (中西医结合护理)
This paper summarized the practice of integrated medical and nursing ward rounds for an elderly patient with chronic renal failure guided by Traditional Chinese Medicine (TCM) theory. Doctors and nurses in charge reported etiology, pathogenesis, nursing issues, goals, measures and outcomes evaluation, and discussed the key issues and existing problems observed during the integrated ward rounds. Integrated ward rounds provides best practice for improving treatment of nursing of patients with chronic renal failure. (本文总结1例以中医理论为指导的老年慢性肾衰竭患者医护一体化护理查房体会。首先组建查房团队, 对患者的病因、病机、护理问题、护理目标、护理措施及护理效果进行汇报、讨论, 以此为慢性肾衰竭患者的治疗和护理提供更完善的方案。)